A flexible contrast enhancement method with visual effects and brightness preservation: Histogram planting. (July 2018) - Chang, Yen-Ching
Hightlights: A contrast enhancement with visual effects and brightness preservation is proposed. The scheme is similar to planting trees, so it is called histogram planting (HP). Equality-spaced and proportionality-spaced distributions (PSDs) are introduced. The proposed method provides optimal overall effects for a wide range of images. HP-PSD without a limit can completely replace the role of histogram equalization. Abstract: Even in contrast, no technique can be claimed to be the best for all kinds of images. When other criteria, such as visual effects and brightness preservation, are considered simultaneously, it is much harder to find the optimal method. For balancing contrast and visual effects, and even brightness preservation, a flexible contrast enhancement method, called histogram planting (HP), is proposed to promote the overall quality of an image. HP is a very promising redistribution method. It first groups histogram components, and then redistributes these grouped grey levels over a specified range through two distributions: an equality-spaced distribution and a proportionality-spaced distribution. For better brightness preservation, each type further performs multiple subhistograms. In terms of contrast and visual effects, and even brightness preservation, experimental results show that the proposed HP-based methods do provide enough contrast enhancement, pleasing appearances and even good brightness preservation for a wide range of images.